Sulfonated-cellulose as catalysts for the efficient conversion of levulinic acid into ethyl levulinate - Reynoso, Rodrigo; Pasquale, Gustavo A.; Ruiz, Diego M.; Páez, Luis A.; Martinez, José J.; Romanelli, Gustavo P. (Universidad Pedagógica y Tecnológica de Colombia, 2024)
This study highlights the use of cellulose sulfuric acid as a heterogeneous, reusable catalyst derived from biomass (Cortaderia Selloana) for synthesizing ethyl levulinate through catalytic esterification of levulinic acid with ethanol. The effects of temperature, catalyst loading, and the molar ratio of ethanol: levulinic acid on the yield of ethyl levulinate were studied to optimize production. A yield of 95% was achieved at 16 hours, 80 °C, and a molar ratio of 3:1 of ethanol: levulinic acid. These results demonstrate that obtaining high yields of ethyl levulinate is feasible using a biomass-derived catalyst.